RECONSTRUCTION OF PALEOGEODYNAMIC CONDITIONS OF CRYSTALLINE ROCKS FORMATION BASED ON PETROPHYSICAL CHARACTERISTIC ANALYSIS. - TOLSTOY, M.; GOZHYK, A.; SUHORADA, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Usage of the idea that rocks and minerals have "physical memory" reflecting thermodynamic conditions of their formation is grounded. Studying of physical properties, composition and structural peculiarities of rocks permits to reconstruct the conditions of crystalline rocks formation